Seroprevalence and risk factors of tick-borne encephalitis in Mongolia between 2016 and 2022 - Dashdavaa Ganbold; Bayarsaikhan Uudus; Naranbat Nyamdavaa; Yeruult Chultemsuren; Amarbayasgalan Zagd; Mungunzaya Tangad; Burmaa Badrakh; Bolorchimeg Baldandorj; Ochgerel Dogsom; Rolomjav Lkunrev; Uyanga Baasandagva; Tsogbadrakh Nyamdorj; et al. (Parasite Epidemiology and Control, 2023)
The tick-borne encephalitis virus (TBEV) is a zoonotic agent that causes severe encephalitis in humans and is transmitted through the bites of infected ticks. Ixodes ticks are the primary vector for TBEV in Mongolia, and approximately 3.4% carry the TBEV. The ticks are capable of not only transmitting these viruses but also serve as excellent reservoir hosts. The Dermacenter tick species may have similar properties. TBEV is a significant cause of virus-related diseases of the central nervous system in many European countries as well as in China, Russia, and Mongolia. Our objectives were to investigate TBEV seroprevalence and infection risk factors in different biogeographical zones and provinces, especially in the highly endemic areas of Mongolia. Serum samples were collected from individuals who experienced tick bites (n = 993) in Mongolia between 2016 and 2022. Enzyme-linked immunosorbent assay of the samples was performed to evaluate for TBEV-specific immunoglobulin (Ig)M and IgG. We analyzed the risk factors and seroprevalence of TBEV infection among these individuals using a cross-sectional, questionnaire-based study. Statistical analyses were performed using a multistage cluster sampling survey design, and all data were analyzed using the R software. TBEV IgM and IgG antibodies were detected in 8.1% (80/993) and 20.2% (201/993) of all serum samples, respectively. The seroprevalence was significantly higher in men (68%, 95% confidence interval [CI]: 1.63–3.13, odds ratio [OR]: 2.25) than in women (p < 0.001). Additionally, the seroprevalence was significantly higher among unemployed (35.0%, 95% CI: 0.31–0.84, OR: 0.51) than employed individuals (p < 0.001). The seroprevalence was the highest among the 25–29 and 35–39-year age groups (11%, 95% CI: 1.29–5.51, OR: 2.65 and 11%, 95% CI: 0.94–3.87, OR: 1.9, respectively), and the lowest in the 65–69-year age group (4%, 95% CI: 0.46–6.15, OR: 1.83) (p < 0.001). Furthermore, the seroprevalence was the highest in Selenge province and the capital city Ulaanbaatar (40%, 95% CI: 1.73–21.7, OR: 5.07 and 28%, 95% CI: 0.51–6.89, OR: 1.57, respectively) and the lowest in Bayan-Ulgii and Dornod provinces (0.5%, 95% CI: 0.06–12.4, OR: 1.33 and 0.5%, 95% CI: 0.03–6.24, OR: 0.72, respectively). TBEV infection incidence remained low in most regions of Mongolia but increased in endemic areas. Furthermore, in the univariate subgroup analysis, age, occupation status, and residential area were significantly associated with TBEV seroprevalence.